The Effect of the Shear Modulus on Planes which is Perpendicular to the Crack’s Edge-planes and Parallel to the Crack’s Front on the ERR in an Orthotropic Rectangular Prism with a Band Crack - Turan Dincel, Arzu (Afyon Kocatepe Üniversitesi, Fen ve Mühendislik Bilimleri Dergisi, 2017)
In this study, a rectangular prism made of an orthotropic material is considered. It is assumed that this prism contains a band crack whose edge-planes are parallel to the upper and lower face planes. It is also assumed that uniformly distributed normal forces are imposed the top and bottom surface of the prism. The aim of this paper is to analyze the effect of the shear modulus on planes which is perpendicular to the crack’s edge-planes and parallel to the crack’s front on the Energy Release Rate (ERR) for different geometric parameters in a rectangular prism. The mathematical formulation of the corresponding boundary-value problem is carried out within the framework of the 3-dimensional linear theory of elasticity. In order to solve this problem, the 3D finite element method was employed. The numerical results are presented.

Bu çalışmada, ortotropik malzemeden yapılmış dikdörtgen prizma ele alınmıştır. Bu prizmanın bir bant çatlak içerdigi ve çatlağın düzlemlerinin, prizmanin alt ve üst düzlemlerine paralel olduğu kabul edilmiştir. Ayrıca prizmanın alt ve üst yüzeylerine düzgün yayılımlı normal kuvvetlerin etki ettiği kabul edilmiştir. Bu çalışmanın amacı; bir dikdörtgen prizmada, çatlak düzlemine dik ve çatlak yüzüne paralel olan kayma modülünün ERR’ye etkisini, farklı geometrik parametreler için incelemektir. Uygun sınır değer problemin matematiksel formülasyonu 3 boyutlu lineer elastistise teorisi çerçevesinde yapılmıştır. Bu problemi çözmek için 3 Boyutlu Sonlu Elemanlar Yöntemi kullanılmıştır. Sayısal sonuçlar sunulmuştur.
Bant Çatlak Içeren Ortotropik Malzemeden Yapılmış bir Dikdörtgen Prizmada, Çatlak Düzlemine Dik ve Çatlak Yüzüne Paralel Kayma Modülünün ERR’ye Etkisi
Keywords: Energy Release Rate; Band Crack; Shear Modulus; 3D Finite Element Method; Orthotropic Material